Temporomandibular Joint Monoarthritis in Rheumatoid Arthritis - A Rare Case Report - Shahin, Md Abu; Karmacharya, Sudhir; Islam, Md Ariful; Khan, Mamun; Morshed, Abdulla Al; Razon, Soleman; Choudhury, Minhaj Rahim (Bangladesh Medical Journal, 2021)
Rheumatoid arthritis (RA) is a chronic, systemic, autoimmune inflammatory disorder that is characterized by joint inflammation, erosive properties and symmetric multiple joint involvement. Temporomandibular joint (TMJ) is very rare to be affected in the early phase of the disease, thus posing diagnostic challenges for the rheumatologist. TMJ complaints are present in about more than 50% of patients of RA. TMJ is usually among the last joint to be involved and is associated with many clinical signs and symptoms of which pain is a major problem leading to inflammation, limited movements, swelling, joint stiffness, and muscle spasm. Here reported case is 64 years old male, ex-smoker, diagnosed case of diabetes mellitus for 7 years, hypertension for 2 years, came to hospital with the complains of pain in left jaw for 1 year. He had no history of other joint pain, morning stiffness or any deformities. The patient was diagnosed as a case of rheumatoid arthritis on the basis of inflammatory monoarthritis with high titer positive RA factor and anti CCP. The patient gradually improved after treatment with methotrexate. Inflammatory markers like ESR dropped down with the clinical improvement. TMJ is seldom joint to be affected first in the disease course. Bangladesh Med J. 2019 Sep; 48 (3): 43-45